Parallel kinetic resolution of methyl (RS)-5-tris(phenylthio)methyl-cyclopent-1-ene-carboxylate for the asymmetric synthesis of (1R,2S,5S)and (1S,2R,5R)-5-methyl-cispentacin - Abraham, E; Davies, S; Docherty, A; Ling, K; Roberts, P; Russell, A; Thomson, J; Toms, S (2008)
Parallel kinetic resolution of methyl (RS)-5-tris(phenylthio)methyl-cyclopent-1-ene-carboxylate with a 50:50 pseudoenantiomeric mixture of lithium (S)-N-benzyl-N-(α-methylbenzyl)amide and lithium (R)-N-3,4-dimethoxybenzyl-N-(α-methylbenzyl)amide provides an efficient entry to the corresponding homochiral methyl (1R,2S,5S)- and (1S,2R,5R)-2-amino-5-tris(phenylthio)methyl-cyclopentane-carboxylate derivatives in >98% de, with subsequent, sequential desulfurisation with Raney Nickel, N-debenzylation and ester hydrolysis furnishing (1R,2S,5S)- and (1S,2R,5R)-5-methyl-cispentacin in high yield, >98% de and >98% ee. © 2008 Elsevier Ltd. All rights reserved.